Optical method for the concrete curing process monitoring with plastic optical fibers - Ferreira, L.
In this work we demonstrate the monitoring of the concrete curing process using a sensing system based on plastic optical fiber. The proposed sensor is based on an unjacketed plastic optical fiber with equally spaced grooves along the core. These grooves on the fiber, depending on the substance surrounding the fiber, enhance the scattering of the propagated optical signal. The transmitted optical power can be used to estimate the water content along the curing period.